Analysis of the legal framework for the Colombian cattle value chain - Burkart, Stefan; Díaz, Manuel Francisco; Enciso, Karen; Charry, Andrés; Muñoz Quiceno, Jhon Jairo; Ruíz, Rocío; Puerta Rodríguez, Cristhian David; Vivas Quila, Nelson J.; Morales, Sandra; Albán López, Noé; Peters, Michael (2017)
The legal framework for the cattle sector can also be considered as public policy for its development. This can be understood as a set of incentives and sanctions, which influences the affected actors and generates changes, not only in internal behaviours and dynamics but also in values. In 2003, Colombia's legal framework for the cattle value chain saw the beginning of a period of major transformations, but it was in 2007 when a radical and complex legislation was presented to introduce the cattle sector into the context of international trade. However, the expected changes of behaviour among actors were not fully achieved by as incompliance could and still can be observed throughout the sector. This study was conducted in 2016 and has the aim to revise the legal framework for the Colombian cattle value chain and to a) analyse the underlying complexities that came with the implementation of rigid legislative processes, and b) to identify the bottlenecks considering the aim of putting the cattle sector into a global context. The methodology consists of two steps: 1) a systematic and chronological compilation of the laws, decrees, resolutions and standards, and 2) an analysis of both the institutional and social evolution of the sector over time, as well as the advances and challenges presented in terms of e.g., traceability, hygiene, animal welfare and sustainability. First results show that although important advances have been made in order to adapt the legal framework to international requirements, these are not sufficient when adequate enforcement and control mechanisms are missing. In addition, the success of public and legislative policies depends to a great extent on the context in which they are applied and the capacities actors have to understand their complexity. This study will serve decision makers in the development of targeted follow-up and improvement processes in order to ensure future competitiveness and sustainability of the cattle sector at international level. It will also serve the value chain actors as guidance on the rules that apply for their specific activity – a valuable source of information given the fact that official information sites are often incomplete.